Pengaruh Program Literasi terhadap Hasil Belajar Siswa SMP Negeri 2 Batudaa - Puluhulawa, Karlina H.; Hasiru, Roy; Toralawe, Yulianti; Panigoro, Meyko; Sudirman Sudirman (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
The purpose of this study was to determine the effect of the literacy programme on student learning outcomes at SMPN 2 Batudaa. The research method used in this research is a quantitative method using a quantitative approach. The data used in this study are primary data obtained from distributing questionnaires or questionnaires to SMPN 2 Batudaa students who meet the standards set by researchers with a sample in this study of 42 students. The results of this study indicate that the Literacy Program has a significant effect on student learning outcomes at SMPN 2 Batudaa, which means that the more students routinely implement the Literacy Program, the more student learning outcomes will increase. The research results of the calculation of the coefficient of determination of this study are 58.4%, which means that the literacy program variable can be explained by the student learning outcomes variable by 58.4% and the remaining 41.6% is explained by other variables not examined in this study.